2021
DOI: 10.1017/s0007114521002981
|View full text |Cite
|
Sign up to set email alerts
|

Associations between free sugar intake and markers of health in the UK population: an analysis of the National Diet and Nutrition Survey rolling programme

Abstract: Recommendations for free sugar intake in the UK should be no more than 5% of total energy due to increased health risks associated with overconsumption. It was therefore of interest to examine free sugar intakes and associations with health parameters in the UK population. The UK National Diet and Nutrition Survey (NDNS) rolling programme (2008-2017) was used for this study. Dietary intake, anthropometrical measurements and clinical biomarker data collated from 5121 adult respondents aged 19-64 years, were sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Mexico also introduced a similar system in 2014, adding a 15% cost to SSBs to discourage consumer purchase [149]. Both countries have observed a reduction in sugar intake since the introduction of the levy, by 4-12% in Mexico [149] and 10% in the UK [54]. In accordance, a meta-analysis also concluded that the implementation of taxes in SSBs around the world is an effective approach for reducing SSB purchase and intake [150].…”
Section: What Can We Do To Reduce Fructose Consumption?mentioning
confidence: 92%
See 4 more Smart Citations
“…Mexico also introduced a similar system in 2014, adding a 15% cost to SSBs to discourage consumer purchase [149]. Both countries have observed a reduction in sugar intake since the introduction of the levy, by 4-12% in Mexico [149] and 10% in the UK [54]. In accordance, a meta-analysis also concluded that the implementation of taxes in SSBs around the world is an effective approach for reducing SSB purchase and intake [150].…”
Section: What Can We Do To Reduce Fructose Consumption?mentioning
confidence: 92%
“…Both the World Health Organization [52] and the UK's Scientific Advisory Committee on Nutrition [53] recommend limiting free sugar intake to less than 5% of overall energy intake. Free sugar is defined as sugar added by the manufacturer, cook, or consumer, plus sugar found in honey, syrup, or fruit juice [49,54]. It is often added as a sweetener to food and drink in the form of sucrose (table sugar) or HFCS (55% fructose), which are commonly used in sugar-sweetened beverages (SSBs) [37].…”
Section: Sources and Consumption Of Fructosementioning
confidence: 99%
See 3 more Smart Citations